If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(x + 3) + -8x = 6 Reorder the terms: 6(3 + x) + -8x = 6 (3 * 6 + x * 6) + -8x = 6 (18 + 6x) + -8x = 6 Combine like terms: 6x + -8x = -2x 18 + -2x = 6 Solving 18 + -2x = 6 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-18' to each side of the equation. 18 + -18 + -2x = 6 + -18 Combine like terms: 18 + -18 = 0 0 + -2x = 6 + -18 -2x = 6 + -18 Combine like terms: 6 + -18 = -12 -2x = -12 Divide each side by '-2'. x = 6 Simplifying x = 6
| 2(x+2)=(x+1)3 | | 2p-5=11 | | R=p/l2 | | 3x+10=2x+23 | | (22c^11)(x^17)(y^14)/(2c^8)(c^15)(y^10) | | 7d+6=42 | | 4t-6=2t+18 | | (5u+3)(5+u)=0 | | -3/9P=-2 | | 8-12(sin^2)x=4(cos^2)x | | -(w+5)+2w-11=-27 | | 4z+2z=5z-3 | | d(t)=360-60t | | 7y+15=4y-6 | | x^2+y^2-8x+2y+8=0 | | 2n-3(5)=n-2(7) | | 2n-3(5)=7(n-2) | | 6(X-4)=32-2x | | 4*1/2−2*2/3= | | -4/3s=7/9 | | 5x-1.5=9c+3 | | 4z-9z=32 | | 30.25+x=35 | | 4x1/2−2x2/3= | | 2x(3)=5(x-1) | | 3(z+8)-2z=23 | | 8x+4=11x+10 | | 3x+5.39=-4.58 | | (-3x^3/y^2)^2 | | x-10x-1=0 | | 9-4x=-5x+5 | | 8d=9d-18 |